Prevalence of malnutrition, anemia, and soil-transmitted helminthiasis in preschool-age children living in peri-urban populations in the Peruvian Amazon - María del Carmen Segoviano-Lorenzo; Elena Trigo-Esteban; Theresa W. Gyorkos; Kariane St-Denis; Fernándo Martínez-De Guzmán; Martín Casapía-Morales (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
Stunting, anemia, and soil-transmitted helminth (STH) infections are major health concerns for children in extremely poor regions of the world, especially rural and periurban ones. This study aimed to determine the prevalence of these three cooccurring conditions in preschool-age children in an extremely poor district on the outskirts of Iquitos, in the Peruvian Amazon, to inform public health actions. Malnutrition was assessed by standard World Health Organization-recommended metrics; anemia, by hemoglobin levels; and STH, by the Kato-Katz technique. Logistic regression analyses were performed to identify the risk factors for our three outcomes of interest. A total of 572 children aged 6-59 months were recruited in March 2019. We found a 31.3% stunting, 47.2% anemia, and 34.1% STH prevalence. Stunting and anemia figures exceeded both regional and national estimates for 2019. Having more children was a risk factor for stunting, whereas married mothers were associated with a lower risk. Risk factors for anemia included younger age and the male sex, whereas those for STH, older age, incomplete vaccination, and a lower socioeconomic status. Mothers' employment outside the home was also associated with a lower STH risk. This recent evidence highlights the need for prompt and integrated clinical attention and public health actions to address both short- and long-term health consequences in this vulnerable child age group. The integration of a monitoring and evaluation framework is important to effectively manage these conditions, optimize resources and accountability, and show their impact.